Tray Dryer's Performance in the Drying of Banana Slices Using LPG and Wood Stove - Devi Yuni Susanti; Joko Nugroho Wahyu Karyadi; Octavia Arini; Septi Agustiani Fajriyah; Sri Rahayoe; Hanim Zuhrotul Amanah (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
An evaluation was carried out on a simple tray dryer of banana slices in the "sale pisang" production. The dryer is designed to use gas fuel and a wood-burning stove as a source of energy. The dryer's performance is analyzed to evaluate its ability to dry the product efficiently and effectively to prevent excessive heat use. The research aims to analyze the temperature distribution in the drying chamber, the profile of the product's moisture content, the drying rate on each shelf, as well as the efficiency of dryers using gas fuel and wood-burning stoves. At an air speed of 0.0176 m3/s, the drying chamber reaches a maximum temperature of 76.2 ℃ using gas and 66.23 ℃ using a wood stove. The use of Liquid Petroleum Gas (LPG) gives an average room temperature of 73.46 ℃, while the furnace gives a less stable pattern with an average temperature of 63.02 ℃. Drying using LPG occurs more quickly with a constant drying rate and a falling rate period of 0.8262%/hour and 0.01504%/hour, higher than using wood fuel which is 0.5482%/hour and 0.0098 %/hour. Within 400 minutes, the product’s moisture content reached 24.64% using LPG and 36.762 using the furnace. The efficiency for heating the drying air is 28.51% and the drying process efficiency is 27% using 8.6 kilograms of LPG as fuel. Meanwhile, using a furnace energy source, the dryer provides a heating efficiency of 15.9% and a drying efficiency of 7.37% with a fuel consumption of 34.12 kg of wood.